2017
DOI: 10.1016/j.ejvs.2016.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Association of Matrix Metalloproteinase Levels with Collagen Degradation in the Context of Abdominal Aortic Aneurysm

Abstract: No significant relationship was found between mRNA and protein and MMP levels. MMPs 9 and 12 were overexpressed in AAA at the mRNA and protein level, and MMP-8 at the protein level. MMP-2 was detected in synthetic SMCs. Collagen I and III showed inverse behaviour in AAA. In particular, MMPs 8, 9, and 12 appear to be associated with collagen I, collagen III, and their degradation products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 36 publications
(25 reference statements)
1
23
0
Order By: Relevance
“…32 However, the association between CKD and AAA remained significant even after accounting for these factors, in addition to a wide range of other potential confounders. Second, matrix metalloproteinases may mediate the CKD-AAA relationship since they play key roles in the pathogenesis of AAA, 33 as well as kidney fibrosis 34 and albuminuria. 35 Third, CKD induces systemic inflammation, a condition considered to increase the risk of AAA.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, the association between CKD and AAA remained significant even after accounting for these factors, in addition to a wide range of other potential confounders. Second, matrix metalloproteinases may mediate the CKD-AAA relationship since they play key roles in the pathogenesis of AAA, 33 as well as kidney fibrosis 34 and albuminuria. 35 Third, CKD induces systemic inflammation, a condition considered to increase the risk of AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a significant correlation between MMP-9 with coronary artery disease [ 20 ] and outcomes after acute myocardial infarction [ 21 ]. The overexpression of MMP-2, -8, -9, and -12 was related to abdominal aortic aneurysm [ 22 ]. Likewise, MMP-8, -9, and -12 seem to be associated with collagen I and collagen III, as well as their degradation products and vascular remodeling [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, matrix metalloproteinase cleave col I while col III level increases 45 . Similarly, it was reported that TNF-alfa, a major pro-inflammatory cytokine, downregulates stromal alfa-SMA45 . Previously we demonstrated that p62 DNA quenches an ovariectomy-induced increase of TNF-alfa levels 29 .…”
mentioning
confidence: 76%